Tinjauan Hukum Implementasi Dana Desa di Desa Boro Kecamatan Sanggar Kabupaten Bima - Ebi Irawan; Erham; Gufran (Jurnal Hukum Lex Generalis, 2025)
The Village Fund is a strategic instrument to promote the development and welfare of rural communities, as stipulated in Law Number 6 of 2014 concerning Villages. However, its implementation is often hampered by aspects of transparency, accountability, and community participation. This article examines the implementation of the Village Fund program in Boro Village, Sanggar District, Bima Regency, from a legal perspective using an empirical juridical approach. The results indicate that implementation is suboptimal due to weak apparatus capacity and minimal community participation. The principles of transparency and accountability have not been fully implemented. Regulatory strengthening, capacity building, and community oversight and participation are needed for the Village Fund to have a significant impact.